2020
DOI: 10.1097/bpo.0000000000001511
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Open Reduction in Pediatric Femur Fractures Treated With Flexible Nails

Abstract: Background: Closed reduction (CR) is sufficient to reduce the majority of femur fractures treated with flexible intramedullary nailing (FIN). No previous study has examined factors associated with failed CR of pediatric femoral shaft fractures treated with FIN. We sought to determine preoperative factors associated with failed CR. We hypothesized that fracture, patient, and surgeon characteristics would impact the need for open reduction (OR). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Results: The mean age was 8.3±1.4 (6)(7)(8)(9)(10)(11) in group 1, 10.2±2.2 (7)(8)(9)(10)(11)(12)(13)(14)(15) in group 2, and 9.7±2.8 (7-15) in group 3. The time of union was 8.0±2.2 weeks (6-16) in group 1, 9.7±2.7 weeks (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in group 2, and 7.1±1.0 weeks in group 3 (6 -9). In group 1, one patient had delayed union, two patients had a valgus deformity, two patients had minor wound site infection, and four patients had shortening of less than 2 cm.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Results: The mean age was 8.3±1.4 (6)(7)(8)(9)(10)(11) in group 1, 10.2±2.2 (7)(8)(9)(10)(11)(12)(13)(14)(15) in group 2, and 9.7±2.8 (7-15) in group 3. The time of union was 8.0±2.2 weeks (6-16) in group 1, 9.7±2.7 weeks (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in group 2, and 7.1±1.0 weeks in group 3 (6 -9). In group 1, one patient had delayed union, two patients had a valgus deformity, two patients had minor wound site infection, and four patients had shortening of less than 2 cm.…”
Section: Methodsmentioning
confidence: 92%
“…A study by Heffernan et al emphasized that open reduction should be initiated in case of prolonged closed reduction in elastic nailing in pediatric femoral fractures. The researchers reported that they had difficulty in reduction, especially in overweight and elderly patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Other work has assessed preoperative factors associated with difficult operative fixation of pediatric femur fractures. In a retrospective study of 85 children treated with flexible intramedullary nailing for isolated femur fractures, Heffernan et al 12 identified 3 factors (high energy mechanism, distal third fracture location, and initial fracture displacement) that predicted the need for open reduction. This study demonstrated the importance of identifying pretreatment risk factors that may necessitate an alternative technique or treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Length unstable fractures are usually spiral, long oblique or comminuted and are often associated with > 2 cm of shortening, with authors recommending the use of EF and submuscular plating for these fracture configurations in children between 5-11 years of age. However, more recently, some authors have recommended the use of FIN's for the management of these fractures (9,11,22,23).…”
Section: Introductionmentioning
confidence: 99%